Spontaneous splenic rupture following stem cell mobilization with G-CSF and plerixafor in AL amyloidosis. Issue 2 (April 2016) - Lessi, Federica; Marson, Piero; Colpo, Anna; Marino, Filippo; Branca, Antonio; Tison, Tiziana; Adami, Fausto
Abstract: Background: AL amyloidosis is a rare plasma cell dyscrasia with multiorgan involvement. Good risk patients are candidate to high dose chemotherapy and autologous stem cell transplantation. However both transplantation and stem cell collection entail significant risk in such patients. Plerixafor is a novel mobilizing agent approved for use in "poor mobilizer" patients with lymphoma and multiple myeloma; experience in systemic amyloidosis patients is limited. Case Report: We describe a case of spontaneous splenic rupture following administration of G-CSF and plerixafor in a patient with AL amyloidosis who previously underwent heart transplantation due to amyloid heart involvement. Results and Conclusion: This is the first report of spontaneous splenic rupture following stem cell mobilization with G-CSF and plerixafor in AL amyloidosis. The role of plerixafor has to be established. AL amyloidosis patients undergoing stem cell mobilization need careful monitoring of signs and symptoms of spontaneous splenic rupture.